Parental Parenting Styles in Patients with Substance Use Disorders: A Study in Songkhla, Thailand - Jaturaporn Sangkool; Chonnakarn Jatchavala (Journal of Health Science and Medical Research (JHSMR), 2016)
Objective: To evaluate the association between drug use and perceived parenting styles among patients with substance use disorders. Material and Methods: This cross-sectional study enrolled patients aged above 18 years, who received services at Thanyarak Songkhla Hospital between the first of April and May the 31st, 2015. The participants were asked to fill out parenting style questionnaires. Data were analyzed by descriptive statistics and logistic regression. Results: A total of 237 patients participated in the study. The response rate was 96% Most of the participants were male (75%), aged between 18-58, with a mean age of 27.1±6.8 years. Sixty-two point nine percent were Buddhist and 34.6% were Muslim. The most, common parenting style was authoritative (70.3%) followed by, authoritarian (6.8%). There was no association between drug use and that of the perceived parenting styles (p-value=0.535). Selfperceived moderately, and poor religious participants were 2.39 times more likely to use drugs [95% confidence interval (95% CI)=1.33, 4.28]. Additionally, participants who had a history of drug use within the family were 2.52 times more likely to use drugs (95% CI=1.21, 5.29). Conclusion: Most patients with a substance use disorder perceive having an authoritative parenting style. There was no specific association between perceived parenting styles and drug use.